1996
DOI: 10.1007/bf00126936
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in natural populations of wild Brassica oleracea as estimated by isozyme and RAPD analysis

Abstract: Naturally occurring populations of wild Brassica oleracea were collected in Spain, France, and Great Britain. Allele frequencies at four isozyme loci were determined for 18 populations, while five populations were screened using five random primers to generate RAPDs. Levels of homozygosity and gene diversity, H, were computed for each population using isozyme data and RAPD data when applicable. Homozygosity levels tended to be higher in smaller populations, which could also be observed as increased numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 15 publications
2
34
2
1
Order By: Relevance
“…This is to be expected for an outcrossing species, and is consistent with other studies done on outcrossing crop species (see e.g., Sanchez et al 2000;Andersen et al 2009). Among wild B. oleracea populations in France, England and Spain a similar value of populationdifferentiation (G ST = 0.37, based on isozyme data) was found (Lannér-Herrera et al 1996), whereas a somewhat lower value (F ST = 0.23, based on AFLP data) was found among wild populations in Britain (Watson-Jones et al 2006).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This is to be expected for an outcrossing species, and is consistent with other studies done on outcrossing crop species (see e.g., Sanchez et al 2000;Andersen et al 2009). Among wild B. oleracea populations in France, England and Spain a similar value of populationdifferentiation (G ST = 0.37, based on isozyme data) was found (Lannér-Herrera et al 1996), whereas a somewhat lower value (F ST = 0.23, based on AFLP data) was found among wild populations in Britain (Watson-Jones et al 2006).…”
Section: Discussionmentioning
confidence: 51%
“…Not much is known about the levels of diversity found in kale landraces, but the diversity and structure of wild populations in England, France and Spain, have previously been investigated (Lannér-Herrera et al 1996;Raybould et al 1999;Watson-Jones et al 2006). With this study we estimate the baseline of diversity in kale landraces and their genetic structure.…”
Section: Introductionmentioning
confidence: 93%
“…Other populations such as those of Onton (n. 33) and Barrika (n. 34) were also originally considered as small but have been shown to extend to both sides of the gulf and appeared two or three times larger when explored from the sea. In comparison with other areas in France and the UK, Spanish populations tend to be relatively smaller (Lann e er- Herrera et al 1996).…”
Section: Discussionmentioning
confidence: 96%
“…In recent studies, fingerprints based on different markers were compared using genotypes from different species. There were both agreements and disagreements in findings based on different markers and species: The study of Brassica oleracea by Lanner-Herrera et al (1996) [11], a moderate spearman's rank correlation (r = 0.38) between RAPD and isozyme distances was found. Russell et al (1997) [12] compared the levels of genetic variation among barley accessions revealed by RFLP, AFLP, SSR, and RAPD, and reported that when the spearman's rank correlation was used, the correlation between SSR and RAPD was 0.235, the highest correlation was found between RFLP and AFLP (0.708).…”
Section: Resultsmentioning
confidence: 99%